Mental Health and Coping Styles of Rural Residents Affected by Drinking Water Shortage in Fars Province: An Ecopsychological Perspective - Khodarahimi, Siamak; Deghani, Haydar; Nikpourian, Mohammadhadi (European Journal of Mental Health, 2014)
The purpose of this study was to examine, in an Iranian sample, the effect of drinking water shortage on the rural residents’ mental health and their coping styles, and to investigate the influences of gender, location of residence, marital status, job and the level of education on these constructs. Participants included 1198 rural residents around the Iranian cities of Darab and Eghlid. A demographic questionnaire, the General Health Questionnaire 28 (GHQ-28), and the Coping Styles with Drinking Water Crisis Scale (CSDWS) were used in this study. The CSDWS is a multidimensional construct with four factors including: (1) optimising water consumption methods, (2) water-free technologies and social changes in life, (3) usage of high-quality technologies in water saving, and (4) emotion-focused avoidant coping styles. Rural residents who had suffered no drinking water shortage had a significantly higher performance of rational coping styles and had a lower psychopathology indicator and a lower performance of emotion-focused avoidant coping styles than rural residents who had experienced drinking water shortage. The effect of location of residence, marital status, level of education and occupation on coping styles and mental health was affirmed in this sample.